2017
DOI: 10.1080/01635581.2017.1263750
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal Proportion ofBlautiasp. is Associated with Clinical Stage and Histoprognostic Grade in Patients with Early-Stage Breast Cancer

Abstract: Improving knowledge about breast cancer etiology is crucial in order to propose prevention strategies for this pathology. Gut microbiota is involved in numerous physiopathological situations including cancers. Although its potential involvement in breast cancer through the alteration of the enterohepatic circulation of estrogens and/or the metabolism of phytoestrogens has been discussed for some time, it remains to be demonstrated. The present study seeks to strengthen this hypothesis by identifying possible l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
114
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 61 publications
4
114
0
1
Order By: Relevance
“…The link between intestinal microbiota dysbiosis and breast cancer has been investigated in several case-control studies, and many hypotheses have been suggested, some of which underline the possible decrease in the metabolic ability of the microbiota and a weakness of the immune system [48]. The results of clinical studies on the relationship between gut microbiota and breast cancer are summarized in Table 1.…”
Section: Is There a Link Between Gut Microbiota And Breast Cancer?mentioning
confidence: 99%
See 3 more Smart Citations
“…The link between intestinal microbiota dysbiosis and breast cancer has been investigated in several case-control studies, and many hypotheses have been suggested, some of which underline the possible decrease in the metabolic ability of the microbiota and a weakness of the immune system [48]. The results of clinical studies on the relationship between gut microbiota and breast cancer are summarized in Table 1.…”
Section: Is There a Link Between Gut Microbiota And Breast Cancer?mentioning
confidence: 99%
“…Several studies have described a higher ratio of Firmicutes / Bacteroidetes (F/B) in obese versus lean subjects, although with controversial results [58]. Significant differences in the absolute numbers of total bacteria and of three bacterial groups ( Firmicutes , Faecalibacterium prausnitzii , and Blautia ) were observed in feces as a function of the body mass index (BMI) of women with early-stage breast cancer, with lower number of bacteria in overweight and obese patients [48]. The lower number of Firmicutes bacteria observed in overweight subjects contrasted with other clinical studies showing an increased ratio (F/B) with obesity [59], no effect [60], or a decreased ratio [61] in obese patients.…”
Section: Is There a Link Between Gut Microbiota And Breast Cancer?mentioning
confidence: 99%
See 2 more Smart Citations
“…Along with genetics, envi ronmental factors contribute to breast cancer development, but what these exact environmental fac tors remain unknown. Although results of their analysis were different from ours, some interesting studies may offer support for certain envi ronmental factors being associated with an increased incidence of breast cancer [36,37] . Urbaniak et al demonstrated that breast tissue contains a diverse population of bacteria [38,39] .…”
Section: Breast Cancermentioning
confidence: 40%